DETERMINANT ANALYSIS RISK FACTORS INCIDENCE OF HEPATITIS B VIRUS INFECTION AT PREGNANT WOMEN - Yuliana, Melyani, Alexander (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
ABSTRACT Pregnant women were susceptible exposed to Hepatitis B Virus infection due to a decrease activity of Sel T in the immune system. The prevalence of Hepatitis B infection in West borneo (2,53%) was higher than the prevalence in Indonesia (1,9%). HBV infection during pregnancy was caused of vertical transmission from mother to child by uteroplacental circulation with HBsAG and DNA of (HBV) as a medium. The purpose of this research is analyze the determines the risk factors of the incidence Hepatitis B virus infection among pregnancy women in Sungai Durian health center years 2018-2020. The type of research used was case control. The population in this research was 133 as a case, 532 not infected women as a control group was done by simple random sampling. The research instrument uses a check list sheet. Prevalence of Hepatitis B in pregnancy by 2.57%. Related variabels with HBV such as age, parity, size of LILA, anemia and environment with p value < 0,05. Age was dominant variable with Odds Ratio 1.608 caused at risk of becoming infected with HBV through saliva and sperm during sexual intercourse, decreased immunity and medical action which can be an entry point for HBV. Keywords : Hepatitis B, infection, risk factor, pregnancy women